Left atrial volume index is superior to left atrial diameter index in relation to coronary heart disease in hypertension patients with preserved left ventricular ejection fraction. (2nd January 2020) - Fu, Ming; Zhou, Dan; Tang, Songtao; Zhou, Yingling; Feng, Yingqing; Geng, Qingshan
ABSTRACT: Objective : Research hypothesis is that left atrial (LA) volume index is superior to LA diameter index for coronary heart disease and LA volume index is important to refine risk stratification. Methods : We retrospectively enrolled 222 asymptomatic non-ischemic patients with hypertension who had stored digital images in 2012. Patients were followed up for coronary heart disease over a median of 3.2 years. The Area under receiver operating characteristic curve for LA parameters with coronary heart disease was evaluated. Cox regression was used to assess the association between left atrial parameters and coronary heart disease. Results : The mean age of patients was 62 years, 45% were men, and mean left atrial diameter, mean left atrial volume, mean LA diameter index, mean LA volume index was 32 mm, 43 ml, 21 mm/m2, 27 ml/m2, respectively. After 3.2 years follow up, 10 patients experienced coronary heart disease. Compared with patients without coronary heart disease, LA diameter index and LA volume index increased in coronary heart disease group (P < 0.05). Multivariate cox regression analysis showed, adjusted for age, sex, smoking, cholesterol, fasting plasma glucose, diabetes, systolic blood pressure, left ventricular mass index, and E/e' ratio, a unit rise in LA volume index was associated with a 15% increase in the risk of coronary heart disease. (HR:1.155; 95% CI 1.002–1.332). Compared with LA diameter index, the area under receiver operating characteristic curve values for predicting coronary heart disease were higher for LA volume index (0.797). Conclusions : Our study showed that LA volume index was superior to LA diameter index. LA volume index had independent prognostic implications in terms of coronary heart disease prediction in hypertension patients with preserved left ventricular ejection fraction.